The Integration of Digital Literacy in Educational Policy: Addressing Global Challenges for Sustainable Education - Af Idatul Amalia (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates the integration of technology and digital literacy into national education policies using a systematic literature review (SLR) guided by the PRISMA protocol. From an initial pool of 675 articles, 53 were selected through rigorous screening. The analysis identifies digital literacy as a central issue, with key challenges including disparities in technological access, inadequate teacher training, and obstacles to policy harmonization. While developed nations like Singapore and Finland have implemented structured approaches successfully, countries such as Indonesia encounter significant barriers, particularly in rural areas with limited infrastructure. The findings underscore the relevance of constructivist theory and pedagogical innovation, highlighting the critical role of teachers and the potential of technology to enhance educational quality. Practical recommendations include sustained professional development for educators, investment in digital infrastructure, and the integration of digital literacy within curricula to achieve inclusive and sustainable educational outcomes. This research provides essential insights for policymakers and educators to navigate the challenges of digital transformation in education effectively